Applicability of accident analysis methods to Chinese construction accidents. (February 2019) - Zhang, Jiangshi; Zhang, Wenyue; Xu, Peihui; Chen, Na
Abstract: Introduction: It is necessary to clearly understand construction accidents for preventing a rise in Chinese construction accidents and deaths. Better analysis methods are required for Chinese construction sector accidents. Methods: Choosing and analyzing a typical construction accident based on four popular contemporary accident causation models: STAMP, AcciMap, HFACS, and the 2-4 Model. Then we evaluated the models' applicability to construction accidents, including their usability, reliability, and validity. Results: STAMP addressed how complexity within the accident system influenced the accident development, and its output makes the responsibilities clearer for the accident. AcciMap described the entire system's failure, the entire accident's trajectory, and the relationship between them. AcciMap showed that the accident was a dynamic developing process, and this method has a high usability. The taxonomic nature of HFACS is an important feature that provides it with a high reliability. In the accident reviewed here, we found that poor management was a critical factor rather than the individual factor in the accident. The 2-4 Model provided detailed causes of the accident and established the relationship among the accident causes, the safety management system, and the safety culture. It also avoided capturing all of the complexity in the large sociotechnical system and revealed a dynamic analysis and developing process. We confirmed that it has a high usability and validity. Therefore, the 2-4Model is recommended for future Chinese construction accident analysis efforts. Practical Applications: The study provides a useful, reliable, and effective analysis method for Chinese construction accidents. Highlights: STAMP, AcciMap, HFACS, and the 2-4Model, were comprehensively analyzed and applied to a typical construction accident. We evaluated the four models' applicability to construction accidents, including their usability, reliability, and validity. The 2-4 Model is recommended for future construction accident analysis efforts.